PENGARUH LARUTAN DAUN BINAHONG (Anredera cordifolia) DALAM AIR MINUM TERHADAP PENAMPILAN AYAM BROILER FASE GROWER - Rizki Ardiansyah; Soegeng Herijanto; Citopartusi Tjahyani; Fani Evadewi (MEDIA PETERNAKAN, 2023)
The research entitled "The Effect of Binahong Leaf Solution (Anredera cordifolia) in Drinking Water on the Appearance of Grower Phase Broiler Chickens" was carried out in the village of Sokaraja Kulon, Sokaraja District, Banyumas Regency. From September 2 to September 16, 2022. The purpose of this study was to determine the effect of giving binahong leaf solution in drinking water on appearance, final body weight, and feed conversion for broiler chickens in the grower phase. he material used was 100 broiler chickens aged 15 days. This study used a completely randomized design (CRD) in one direction with a treatment consisting of one control treatment and three different treatments. The treatments tried were: P0: 1 liter of drinking water without binahong leaf solution, P1: 100 ml of binahong leaf solution given 20 ml/liter of drinking water/day, P2: 200 ml of binahong leaf solution given 40 ml/liter of drinking water/day, P3: 300 ml of binahong leaf solution given 60 ml/liter of drinking water/day. he variables observed were final body weight and feed conversion. The results of statistical analysis showed that the treatment had no significant effect (P>0.05) on the final weight and feed conversion of broiler chickens in the grower phase. The conclusion of the study was that the administration of binahong leaf solution at levels of 20, 40 and 60 ml/liter of drinking water/day had the same effect on final body weight and feed conversion for broiler chickens in the grower phase. Keyword: Broiler chickens, appearance, binahong leaf solution (Anredera cordifolia).